Real-World Effectiveness of Disease-Modifying Therapies in Korean Patients with Relapsing Multiple Sclerosis - Kim, Su-Hyun (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: This study assessed the long-term outcomes of disease-modifying therapies (DMTs) in Korean multiple sclerosis (MS) patients treated in real-world clinical settings in Korea. METHODS: We retrospectively evaluated the medical records of 160 patients with an initial diagnosis of clinically isolated syndrome or relapsing-remitting MS who were treated for at least 2 years. A status of 3 for no evidence of disease activity (NEDA3) was defined as no relapse, disability progression, or active lesions in annual magnetic resonance imaging (MRI) evaluations. RESULTS: Patients who were initially treated with interferon β (n=152), glatiramer acetate (n=6), or teriflunomide (n=2) were included. The mean disease duration was 8.2 years. Compared to pretreatment, annualized relapse rates were significantly reduced after treatment [from 1.0±0.8 to 0.2±0.4 (mean±standard deviation), p<0.001]. At the follow-up, 79 patients (49%) had changed their treatment regimen due to lack of efficacy (33%), side effects (14%), or other reasons (2%). Disability progression was observed in 18% of the patients over a mean treatment duration of 5.7 years. After 2 years, NEDA3 was observed in 38% of the patients. Loss of NEDA3 at 2 years was associated with long-term disability progression [odds ratio (OR)=17.975, p=0.003]. Poor response to first-line treatment was independently associated with a delay in treatment from disease onset (OR=1.238, p=0.049) and 10 or more brain lesions in the initial MRI (OR=3.648, p=0.047). CONCLUSIONS: This study has provided real-world evidence that DMTs are effective in reducing disease activity and disability progression in Korean MS patients.